Shakespeare in the Undiscovered Bourn : Les Kurbas, Ukrainian Modernism, and Early Soviet Cultural Politics. - Makaryk, Irena (University of Toronto Press, 2014)
Shakespeare in the Undiscovered Bourn examines the complexities of the Soviet encounter with Shakespeare. It thus makes an important contribution to the studies of theatre, cross-culturalism, modernism, and postcolonialism.